2023
DOI: 10.1186/s13244-023-01395-9
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning model using chest X-ray for identifying TB and NTM-LD patients: a cross-sectional study

Abstract: Background Timely differentiating between pulmonary tuberculosis (TB) and nontuberculous mycobacterial lung disease (NTM-LD), which are radiographically similar, is important because infectiousness and treatment differ. This study aimed to evaluate whether artificial intelligence could distinguish between TB or NTM-LD patients by chest X-rays (CXRs) from suspects of mycobacterial lung disease. Methods A total of 1500 CXRs, including 500 each from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The pre-trained model was successfully applied to retinal optical coherence tomography and pneumonia diagnosis [34]. In our previous studies, we also successfully demonstrated the capability of fine-tuning in improving model performance on external cohort [10,18].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The pre-trained model was successfully applied to retinal optical coherence tomography and pneumonia diagnosis [34]. In our previous studies, we also successfully demonstrated the capability of fine-tuning in improving model performance on external cohort [10,18].…”
Section: Discussionmentioning
confidence: 96%
“…Deep learning involving convoluted neural network (CNN) is novel and emerging technique for breathprint analysis [8,9]. Some analytic approaches such as transfer learning and data augmentation have been applied in other aspects of biomedical imaging researches [10]. These methods could potentially propagate sample size, enhance performance and ameliorate the drop of performance in domain shift [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a cross-sectional study published in Insights Imaging in 2023 developed a deep neural network (DNN) algorithm to detect the X-ray results of TB patients, distinguishing between active PTB and nontuberculous mycobacterial lung disease (NTM-LD). The study demonstrated that the DNN model exhibited stable performance in detecting TB and mycobacterial lung disease based on the area under the curve (AUC) [ 258 ]. Furthermore, various deep learning algorithms, including decision trees, random forests, support vector machines, Bayesian methods, logistic regression, and hierarchical clustering, have been applied in the differentiation and diagnosis of LTBI and ATB, substantially enhancing the diagnostic efficacy [ 259 , 260 , 261 , 262 , 263 , 264 , 265 ].…”
Section: Challenges and Prospects In The Research Of Novel Tb Vaccinesmentioning
confidence: 99%